2012
DOI: 10.1111/j.1600-0838.2012.01516.x
|View full text |Cite
|
Sign up to set email alerts
|

The soy isoflavone genistein inhibits the reduction inAchilles tendon collagen content induced by ovariectomy in rats

Abstract: The objective of this study was to evaluate effects of genistein and moderate intensity exercise on Achilles tendon collagen and cross-linking in intact and ovariectomized (OVX) female Sprague-Dawley rats. Rats were separated into eight groups (n=9 per group): intact or OVX, treadmill exercised or sedentary, genistein-treated (300 mg•kg−1•day−1) or vehicle. After 6-weeks, tendons were assayed for the collagen-specific amino acid hydroxyproline and hydroxylyslpyridinoline (HP). Collagen content was not influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…It should be clarified in future studies whether the changes observed in aged female mice are also present in aged male mice. Additionally, it has been suggested that treatment with phytoestrogens and exercise loading are effective for the maintenance of tendon mass and mechanical properties (35,36). Therefore, it would be important to determine whether phytoestrogens and exercise suppress and exhibit protective actions on the aging-associated decrease in the expression of collagen and tenogenic markers observed in the present study.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…It should be clarified in future studies whether the changes observed in aged female mice are also present in aged male mice. Additionally, it has been suggested that treatment with phytoestrogens and exercise loading are effective for the maintenance of tendon mass and mechanical properties (35,36). Therefore, it would be important to determine whether phytoestrogens and exercise suppress and exhibit protective actions on the aging-associated decrease in the expression of collagen and tenogenic markers observed in the present study.…”
Section: Discussionmentioning
confidence: 83%
“…Stenosing tenosynovitis is a common tendinopathy in flexor tendons, and females are 6 times more likely to be affected compared with males (33,34). In addition, a previous study demonstrated that estrogen exhibits a protective effect on the tendon extracellular matrix, in particular collagen synthesis in females (35). Therefore, in the present study, to evaluate the aging-associated changes in tendons, postmenopausal female mice (78 weeks of age) were utilized.…”
Section: Discussionmentioning
confidence: 99%
“…HPLC. Patellar tendon collagen content was determined via quantification of hydroxyproline via fluorometric detection, as previously described with minor modifications (10,11,28). After derivatization, samples were injected onto a HPLC instrument (LC-20AB and SIL-20, Shimadzu Scientific Instruments, Columbia, MD).…”
Section: Methodsmentioning
confidence: 99%
“…Hydroxylyslpyridinoline (HP) cross-linking content was determined as previously described (10,11,28). A 500-l aliquot of the hydrolyzed sample was evaporated to dryness overnight at ambient temperature (Thermo Fisher Savant SPD131DDA SpeedVac Concentrator).…”
Section: Methodsmentioning
confidence: 99%
“…One unit of insulin was administered subcutaneously twice a week or as desired. The dose of genistein was chosen based on recent published studies showing that genistein at 300 mg/kg was useful as pharmacological approach for the treatment of diabetic-induced cardiomyopathy [28][29][30]. The body weight of the rats was measured weekly using sensitive digital balance.…”
Section: Experimental Groupsmentioning
confidence: 99%